2003
DOI: 10.1093/jjco/hyg084
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfractionated Radiation Therapy for Hypopharyngeal Carcinoma Compared with Conventional Radiation Therapy: Local Control, Laryngeal Preservation and Overall Survival

Abstract: This study suggests that hyperfractionated radiation therapy for hypopharyngeal carcinoma is promising with a better local control rate, a greater laryngeal preservation rate and a relatively better overall survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Based on the results of studies exploring the role of altered fractionation regimens in head and neck cancer, or exclusively in hypopharyngeal cancer, and the significant improvement in the rates of local control for hypopharyngeal lesions of T2 or greater, and possibly also for T1 tumors reported by several authors, [73][74][75][76][77] it can be presumed that besides the lack of data regarding the subsites of primary hypopharyngeal lesions treated, there would also be an expected benefit in terms of increased rates of local control for patients with early stage pyriform sinus carcinomas by the use of altered fractionation as compared to conventionally fractionated radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of studies exploring the role of altered fractionation regimens in head and neck cancer, or exclusively in hypopharyngeal cancer, and the significant improvement in the rates of local control for hypopharyngeal lesions of T2 or greater, and possibly also for T1 tumors reported by several authors, [73][74][75][76][77] it can be presumed that besides the lack of data regarding the subsites of primary hypopharyngeal lesions treated, there would also be an expected benefit in terms of increased rates of local control for patients with early stage pyriform sinus carcinomas by the use of altered fractionation as compared to conventionally fractionated radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that hyperfractionation and accelerated fractionation significantly improve the local control of hypopharyngeal cancers of T2 or greater, and possibly also for T1 tumours. (Fu et al, 2000;Garden et al, 1996 ;Niibe et al, 2003 ;Parsons et al, 1984 ;Rosenthal & Ang, 2004).…”
Section: Radiotherapymentioning
confidence: 99%
“…Regarding different therapy concepts for stage I and II hypopharyngeal carcinomas, the 5-year survival rate averages between 52% and 77% for radiotherapy (with or without concomitant chemotherapy) [201], [202], [203], [204], between 56% and 77% for supraglottic or supracricoid hemilaryngopharyngectomy (with or without induction chemotherapy, neck dissection or postoperative radiotherapy) [205], [206], [207], [208], and between 70% and 73% for transoral laser microsurgery (with or without neck dissection or postoperative radiotherapy) [209], [210], [211]. The 5-year survival rates for stage III and IV hypopharyngeal carcinomas are 19%–37% for radiotherapy (with or without concomitant chemotherapy) [212], [213], [214], [215], and 47%–59% for transoral laser microsurgery (with or without neck dissection or postoperative radiotherapy) [209], [210]. Induction chemotherapy followed by radiotherapy achieved a 5-year survival rate of 38% in stage III and IV hypopharyngeal carcinomas [216].…”
Section: Carcinomas Of the Hypopharynxmentioning
confidence: 99%